1987
DOI: 10.1520/jfs12404j
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Lysergide (LSD) from Related Ergot Alkaloids and Its Identification in Forensic Science Casework Samples

Abstract: The separation of lysergide (LSD) from related ergot alkaloids, and its isomer lysergic acid methylpropylamide (LAMPA), has been investigated using the techniques of capillary gas chromatography and high performance liquid chromatography (HPLC). Capillary gas chromatography using fused silica nonpolar bonded phase columns gave good discrimination, and retention indices for several ergot alkaloids have been measured. The applicability of this technique to the analysis of illicit LSD preparations has been demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The result from applying the GC‐triple quadrupole‐MS approach (method 1) to the analysis of underivatized LSD (RI = 3140, 23.51 min, DB‐1), MIPLA (RI = 3157, 23.78 min, DB‐1) and LAMPA (RI = 3183, 24.48 min, DB‐1) is shown in Figure 2a where it can be seen that the separation between LSD and LAMPA was considered satisfactory based on the retention time difference of about 1 min. This was in agreement with many other investigators who also demonstrated a successful separation under GC conditions 8,14,19,20,22,24,25 in addition to those GC‐based studies that used LAMPA as an internal standard 33,40,41,43 . Even though the differentiation between LSD and LAMPA was straightforward, the inclusion of MIPLA revealed that it eluted between LSD and LAMPA under these conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The result from applying the GC‐triple quadrupole‐MS approach (method 1) to the analysis of underivatized LSD (RI = 3140, 23.51 min, DB‐1), MIPLA (RI = 3157, 23.78 min, DB‐1) and LAMPA (RI = 3183, 24.48 min, DB‐1) is shown in Figure 2a where it can be seen that the separation between LSD and LAMPA was considered satisfactory based on the retention time difference of about 1 min. This was in agreement with many other investigators who also demonstrated a successful separation under GC conditions 8,14,19,20,22,24,25 in addition to those GC‐based studies that used LAMPA as an internal standard 33,40,41,43 . Even though the differentiation between LSD and LAMPA was straightforward, the inclusion of MIPLA revealed that it eluted between LSD and LAMPA under these conditions.…”
Section: Resultssupporting
confidence: 91%
“…When implementing a single quadrupole LC‐Q‐MS method to the analysis of LSD, MIPLA, and LAMPA, it was found that LSD (29.95 min) could be conveniently separated from MIPLA and LAMPA (30.52 min) but MIPLA and LAMPA could not be separated (Figure 6a) even after attempts to optimize the method and conditions further. LC‐based separations between LSD and LAMPA have been reported in the literature 8,10,14,17,37,60 . In some cases, the separation between LSD and LAMPA was unsuccessful under the conditions used 16 whereas other reports showed a partial overlap still suitable for differentiation 11–13,15 .…”
Section: Resultsmentioning
confidence: 99%
“…4. (Dagnino et al 1991) Japp et al (1987) to develop a GC system to separate these compounds. The GC conditions are described in Table 4.…”
Section: Ergot Indole Alkaloidsmentioning
confidence: 99%
“…Total ion chromatogram of metoprolol (l), moperone (2), haloperidol(3), pipamperone (internal standard, 4), aceperone (5), benperidol and droperidol(6+7) in extracts of samples of spiked human plasma (capillary column of methyl phenyl silicone).…”
mentioning
confidence: 99%